The Influence of Retail Mix (Price, Product, Location) on Purchasing Decisions (Case Study of MR.DIY Supermarket at Ramayana Department Store Pematang Siantar) - Sonya Basa Odelia Hutagaol (International Journal of Integrated Science and Technology, 2023)
The evolution of contemporary retail is accelerating. The growing number of shoppers who demand an easy and comfortable shopping experience has an impact on the growth of modern retail. The purpose of this research is to ascertain how the retail mix affects consumers who shop at the MR.DIY supermarket in the Ramayana Pematang Siantar department store. In this research, the retail mix is divided into three categories: price, product, and location. This research uses quantitative methods. A Likert scale was utilized for measuring, and a snowball sample method with 100 participants was used for sampling. Simple linear regression tests and multiple regression tests are used in data analysis with the SPSS 21 program. Based on the calculations, it can be deduced that 3,424, 3,800, and 3,375, respectively, of the 3,424 purchasing decisions are partially influenced by the price variable, the product variable, and the 3,800, 3,800, and 3,375, respectively, by the location variable. In the meantime, 29.513's purchasing decisions are simultaneously impacted by the retail mix variables of price, product, and location. This means that the higher purchasing decisions that result from a better retail mix will raise customer loyalty levels.In the meantime, 29.513's purchasing decisions are simultaneously impacted by the retail mix variables of price, product, and location. This means that the higher purchasing decisions that result from a better retail mix will raise customer loyalty levels.